ACCURACY OF NURSE TRIAGE IN THE EMERGENCY DEPARTMENT OF BANGIL PASURUAN HOSPITAL - Faisal Ibnu; Umi Azizah Kusumaningrum (Universitas Pesantren Tinggi Darul Ulum, 2023)
Triage nurses should carry out the triage process simultaneously, quickly, and directly according to the patient's complaints and avoid delays in treatment in critical conditions. The phenomenon that occurs in the Emergency Installation is that the application of triage has not been carried out optimally so that there are still many patients who do not get fast and appropriate treatment according to their condition. The purpose of this study was to determine the accuracy of nurse triage at the Emergency Installation of Bangil Pasuruan Hospital. The design of this study is descriptive. The study sample was 30 nurses taken through total sampling techniques. The instrument used is an observation sheet. The results showed that almost all respondents were right in determining triage, namely 26 people (86.7%), and those who were not right in determining triage were 4 people (13.3%). These results show that almost all nurses have decided on triage appropriately. The proper triage decision-making is based on the frequency of the breath, palpable pulse or not and the patient's state of mental status or consciousness as well as the ability to walk to distinguish between yellow and green triage. Keywords: Accuracy, Triage nurse, Emergency room.